A Handheld Robot for Endoscopic Endonasal Skull Base Surgery: Updated Preclinical Validation Study (IDEAL Stage 0) - Starup-Hansen, Joachim; Newall, Nicola; Dimitrakakis, Emmanouil; Khan, Danyal Z.; Dwyer, George; Iyengar, Keshav; Psychogyios, Dimitrios; Hanrahan, John G.; Sinha, Siddharth; Booker, James; Stoyanov, Danail; Marcus, Hani J. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background and Objectives Endoscopic endonasal surgery (EES) has become increasingly popular, yet anatomical constraints posed by the nose and limitations of nonarticulated instruments render EES technically challenging, with a steep associated learning curve. Therefore, we developed a handheld robot to enhance dexterity in endoscopic neurosurgical procedures. A previous trial of the robot demonstrated its potential advantages in endoscopic neurosurgery but also the need for improvements. In this study, we assess the feasibility, acceptability, and comparative performance of the updated robotic prototype (version 0.2) against standard instruments in a preclinical phantom and cadaveric trial.Methods Ethical approval was received. Participants were stratified according to their neurosurgical experience. In the phantom study, a randomized crossover design compared the robot against standard instruments at a phantom tumor resection task. Statistical analysis was performed using Mann–Whitney U tests and paired t-tests. In the cadaver-based user study, participants evaluated the device's functional domains through a qualitative interview design.Results In the phantom study, the device demonstrated a learning curve: initial resection attempts favored the traditional instrument (84% vs. 59%, p = 0.055), but parity was achieved by the fifth attempt (80% vs. 83%, p = 0.76). Acceptability was evident, as most clinicians (7/8) preferred the robot for its superior range, ergonomics, and precision. Also, the robot exhibited a diminished cognitive workload. The cadaveric study underscored the robot's clinical feasibility, through sufficient workspace reach and force delivery.Conclusion: Overall, our robot demonstrates promising acceptability and feasibility for endoscopic neurosurgery, yet further iterative developments are required before proceeding to in-human clinical trials.
Keywords: endoscopic neurosurgery; pituitary surgery; robotic surgery; skull base